Effect of Nutritional Counseling and Stretching Exercises Programs on Nutritional Status and Nutrition Intake - Nazhif Gifari; Mury Kuswari; Dea Azza (University of Darussalam Gontor, 2018)
The objective of this study was to analyze the effect of nutritional counselling and stretching exercises programs on nutritional intake and nutritional status at Indofood Sukses Makmur Company, Jakarta. The design of this study was used quasy experiment research using one group pre test and post test design and the subject used was purposive sampling on 35 employees by anthropometric measurement, body compotision and food recall 2x24 hours. Interventions provided are nutritional counselling through meetings once per month and social media by whatsapp apps 3-5 times per week and stretching exercises program 10 times per week for 14 weeks. The result showed that there were significantly decreased in weight (1.6 kg), Body Mass Index (BMI) of 0.7 kg/m2 and Body Fat Percentage (BFP) of 0.8% with p-value<0.05. The increase nutrient intake (energy, protein, fat and carbohydrate) but only protein intake was significant effect (p<0.05) of intervention. This implied that combination of nutritional counselling and stretching exercises programs was effective to maintenance nutritional status.